Fire exposure behavior of epoxy reinforced with jute fiber applied to ceramic tiles for a ventilated facade system - Ribeiro,Aline (2019)
Civil construction seeks to increase the useful life of the facades of buildings. Installing a ventilated facade is one way to accomplish this due to aesthetic and technical advantages. Ceramic tiles are the main products used as the covering. To the back face of a tile, a bidirectional screen of glass fiber is adhered using epoxy resin. This set forms a composite for security reasons. During the last decade, there has been an increase in the substitution of composites of synthetic fibers with those of natural fibers. The present work compares the fire-resistant behavior of glass fiber with that of jute fiber applied to ceramics installed in ventilated facade. The following conjoint composites were produced: glazed porcelain tile, epoxy resin, glass fiber and jute fiber screens. In this work, it was verified that the jute fiber did not present advantages regarding the exposure to fire in comparison with the glass fiber.